Analysis of workload and role conflict on work stress and their implications on turnover intention - Suseno, Bambang Dwi; Basrowi, Basrowi; Kuwartika, Yuni (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2023)
The aim of the research is to analyze the influence of workload, role conflict on work stress and its implications for honorary nurse turnover. The method used was quantitative research with a sample size of 160 honorary nurses, data was obtained using a questionnaire and analyzed using smart PLS 3.0. The research results found that work stress was influenced by role conflict, not because of workload. Other findings reveal that turnover intention is influenced by role conflict and work stress, while workload does not affect turnover intention. So work stress mediates the effect of role conflict on turnover intention, and also mediates the effect of workload on turnover intention. This research is able to provide a theoretical contribution regarding the pseudo-effect of work stress in mediating the indirect influence of workload and role conflict on turnover intention. Managers who want to reduce turnover intention can evaluate role conflict and workload to reduce work stress